2022
DOI: 10.1186/s12962-022-00355-2
|View full text |Cite
|
Sign up to set email alerts
|

What are the short-term annual cost savings associated with kidney transplantation?

Abstract: Background Kidney transplantation (KT) is often reported in the literature as associated with cost savings. However, existing studies differ in their choice of comparator, follow-up period, and the study perspective. Also, there may be unobservable heterogeneity in health care costs in the patient population which may divide the population into groups with differences in cost distributions. This study estimates the cost savings associated with KT from a payer perspective and identifies and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Also, studies have shown that kidney transplantation is associated with decreases in mean annual health care costs compared with dialysis. 11 This emphasizes that there are likely cost savings that accompany policy changes that result in a greater number of dialysis patients receiving a deceased donor kidney transplant. In contrast, if the policy leads to a reduction in the deceased donor kidney transplant rate, it will expectedly lead to a decrease in both QALYs and total LYs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies have shown that kidney transplantation is associated with decreases in mean annual health care costs compared with dialysis. 11 This emphasizes that there are likely cost savings that accompany policy changes that result in a greater number of dialysis patients receiving a deceased donor kidney transplant. In contrast, if the policy leads to a reduction in the deceased donor kidney transplant rate, it will expectedly lead to a decrease in both QALYs and total LYs.…”
Section: Discussionmentioning
confidence: 99%
“…The annual inpatient costs before and after KT and costs for insured physician services before and after KT varied by whether the patient received an organ from a deceased or a living donor (Table 1 ). We sourced these costs from a Canadian study [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…LEADDR currently has multiple articles in various stages of publication: eleven published, one accepted, three under peer review, and nine publications in progress. 10,15,[21][22][23][24][25][26][27][28][29] Included in those projects is an ongoing interrupted time series evaluating the quantitative impact of legislative change on donation and transplantation rates. Intentionally, this data has not been reported at this time, based on experiences from other jurisdictions that the full impact of such a change often does not occur until three to five years post implementation.…”
Section: Evaluation Of Successmentioning
confidence: 99%